The effect of micron sized wood fibers in wood plastic composites - W. Gallagher, Lance; G. McDonald, Armando (Maderas. Ciencia y Tecnología, 2025)
The popularity and demand for wood plastic composites (WPC) has focused research on fiber properties associated with performance. In this study, maple wood fibers (WF) were ball milled and classified into discrete size fractions. Fiber analyses showed only three distinct WF size classes (80-100, 100-200 and <200 mesh). High density polyethylene (HDPE) based WPC were made from classified WF (10 to 50%). The effect of WF size, loading, and maleated polyethylene (MAPE) coupling agent on WPC rheological behavior (torque rheometry and melt flow rate (MFR)) and flexural properties were examined. The WPC MFR decreased with wood loading, increased with a reduction in WF size. The modulus of rupture (MOR) was shown to increase with a reduction in WF size and increase with the addition of MAPE. The increase in MOR is likely due to an increase in the interfacial interaction between the polymer and WF. Modulus of elasticity (MOE) was shown to increase with an increase in wood loading and decrease with a decrease in WF size. The toughness of the WPC was shown to increase with a decrease in WF size and increase upon addition of MAPE.